Impact of applied artificial intelligence to digital photography in the work of the graphic designer - Lazo Pastó, Orlando Rafael (2025)
T This study analyzes the current relationship between artificial intelligence (AI) and digital photography. The objective was to determine the impact of AI applied to digital photography on the work of graphic designers. The study was conducted through an analysis of documentary sources, complemented by interviews with Ecuadorian graphic designers who produce AI-generated photographs. This approach identified significant changes resulting from the convergence of AI and photography, presenting advantages for design professionals, such as task simplification in editing and a high degree of realism. However, ethical dilemmas also emerge, related to visual reality manipulation, privacy, and the authenticity of the resulting photographic image. Discussing these issues, which are part of the ongoing debate on AI-generated images and their impact on the field of graphic design, may help clarify ethical and professional questions surrounding the future of this phenomenon.